Implementation of Curriculum Management in Increasing the Relevance and Effectiveness of Learning at Madrasah Aliyah - Lukman Sholeh; Khalifatun Nisa; Abdurrohman Nur Ahsani; Nur Wasilah; Virgin Sabrina el-Islamy; Fanil Fanil (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to enhance the pertinence and efficacy of Learning by implementing curriculum management. This study employs a descriptive qualitative methodology with a case study approach. The objective of this research is to comprehensively and thoroughly describe the implementation of curriculum management in enhancing the relevance and effectiveness of learning at Madrasah Aliyah Nurul Jadid Paiton Probolinggo. The data collection methods employed in this study encompassed observation, interviews, and documentation analysis. The research informants consisted of principals, curriculum departments, teachers, and fifteen students who served as responders. The data analysis procedures employed with Miles and Huberman data analysis involve the processes of data reduction, data presentation, and drawing inferences. The study findings indicated that the implementation of Curriculum Management in Madrasah Aliyah Nurul Jadid educational institutions comprises various components, namely Content and skills, evidence-based interventions, instructional settings, Classroom Management and Construction Procedures, Evaluation of progress, Effective binding learning when there are several components, management of learning applications, communicative processes, responses from students, and learning activities.